Public policy jako narzędzie interwencji państwa w rynek pracy na przykładzie Polski po 1989 roku - Popiołek, Renata (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The article describes the public policy as a tool of state’s intervention in the policy of the labour market. The main example is Poland 25 years after the transformation of the political system. This article is an attempt to reflect on the phenomenon of public policy in free Poland. It’s the analysis of definitions, sectorial policies created to solve the sectoral problems and the process of intervention in the labour market policy in Poland over the last 25 years.